A novel multiscale neutron diffraction based experimental approach for granular media. Issue 2 (24th March 2019) - Athanasopoulos, S. D.; Hall, S. A.; Kelleher, J. F.
Abstract : The complexity of granular (geo-) materials is associated with the mobility and interaction of their constituent particles. Under the effect of loading, these materials exhibit a highly inhomogeneous behaviour, which might vary significantly as the loading develops (i.e., certain grain assemblies take up the load whilst other, neighbouring assemblies fall into states of lower load). To that end, understanding the (micro-) mechanisms related to the distribution and evolution of forces/stresses through granular media requires appropriate, spatially-resolved measurements. Neutron Strain Scanning (NSS) is an experimental technique based on diffraction measurements that has been successfully used in recent years to infer force/stress distribution in granular materials under load, by measuring the crystallographic strains of grains. In this work, first results from a new experimental approach involving simultaneous NSS and Digital Image Correlation (DIC) of quartz sand under load in a specially designed plane-strain apparatus are presented. The combined use of these techniques allows the investigation of deformation mechanisms in granular media, such as sand, at different scales. Therefore, a completely novel multiscale analysis of granular (geo-) materials can be made; i.e., associating the traditional macroscale measurements to the mesoscale characterisation of the strain field (through DIC) and the inferred microscale stress distribution (through NSS).